Decision support system model using FIS Mamdani for determining tire pressure - Rusliyawati Rusliyawati; Agus Wantoro (Jurnal Teknologi dan Sistem Komputer, 2021)
Tire air pressure is very important in driving, providing comfort, safety, and efficiency in fuel consumption. This study aims to create a model that can determine the measurement of tire air pressure. The model was developed based on the Mamdani FIS with five input parameters: load weight (load capacity), weather, mileage, rim diameter, and tire thickness. Mamdani inference generates front and rear tire air pressure. The calculation of tire pressure using the system was compared with a manual that only considers the vehicle load. This comparison shows the difference in the mean size of 1.24% for the front tire pressure and 2.17% for the rear tire. The system can provide recommendations for tire air pressure by considering several parameters in addition to vehicle load.